Flipped classroom with gamified technology and paper-based method for teaching vocabulary - Damar Isti Pratiwi; Sri Wuli Fitriati; Issy Yuliasri; Budi Waluyo (Asian-Pacific Journal of Second and Foreign Language Education, 2024)
Abstract While gamified technology integration in vocabulary instruction within a flipped classroom has yielded beneficial teaching outcomes, specific studies have raised concerns about potential adverse effects linked to this approach. As a result, conducting a comparative analysis between gamified technology and conventional paper-based methods within the flipped classroom framework has become essential. This analysis aims to foster the development of a targeted teaching approach that adeptly addresses the unique needs of students. This study employed a sequential explanatory research design to examine the effectiveness of flipped classroom with gamified technology and paper-based method in teaching vocabulary to students with different proficiency levels. Quantitative data was gathered from a pretest and a posttest, whilst qualitative data was collected through teachers’ guided reflection. Using Academic Word List (300 target words), control groups employed a paper-based, while experimental groups applied gamified technology (Quizlet, Kahoot!, Quizizz, Socrative, and Google Form), which lasted 10 weeks. The participants were 144 non-English major students who took a general English course in the 2nd semester of 2023. Quantitative data analysis ran in SPSS 25 using Paired Sample t-Test and One-way ANOVA. The qualitative data were analyzed using thematic progression. The results showed that gamified technology did not affect students’ learning outcomes, while the paper-based method resulted conversely. It revealed that the paper-based method is more effective than gamified technology for students in general, with low proficiency and high-proficiency level. Further, teachers’ beliefs admitted distinctive issues that gamified technology was more effective for high-proficiency learners, whereas paper-based was more effective for low-proficiency learners. The difference analysis of quantitative and qualitative data sheds light on discussing threats while implementing gamified technology and possible solutions.